Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3174158
|View full text |Cite
|
Sign up to set email alerts
|

In a New Land

Abstract: Framed within the theoretical lens of positive and negative security, this paper presents a study of newcomers to Sweden and the roles of mobile phones in the establishment of a new life. Using creative engagement methods through a series of workshops, two researchers engaged 70 adult participants enrolled into further education colleges in Sweden. Group narratives about mobile phone use were captured in creative outputs, researcher observations and notes and were analysed using thematic analysis. Key findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Within HCI and CSCW literature, the power relationships that are enforced and created through the digitisation of aid and refugee services have been primarily focused on the sharing of personal information [12,57] and connecting to bureaucratic processes [13]. The uniquely precarious position that refugees and asylum seekers find themselves in and their dependency on aid organisations is attributed to their lack of agency in controlling their personal information [12,57].…”
Section: Everyday Security Power Asymmetries and Shifting Responsibilitiesmentioning
confidence: 99%
“…Within HCI and CSCW literature, the power relationships that are enforced and created through the digitisation of aid and refugee services have been primarily focused on the sharing of personal information [12,57] and connecting to bureaucratic processes [13]. The uniquely precarious position that refugees and asylum seekers find themselves in and their dependency on aid organisations is attributed to their lack of agency in controlling their personal information [12,57].…”
Section: Everyday Security Power Asymmetries and Shifting Responsibilitiesmentioning
confidence: 99%
“…However, studies reflecting on the use of design methods with refugees are few and limited to workshops conducted in formal spaces or spaces (i.e. a room in a school [13,15]). Conducting design research with Syrian refugee women residing in informal settlements in rural Lebanon precludes the use of such spaces.…”
Section: Introductionmentioning
confidence: 99%
“…One participant indicated that, "You are the first people that come back to visit us"[CS1.3]. This was contrasted with other researchers that participants have engaged with, "People come and ask us questions and leave us" [Cs1 13]…”
mentioning
confidence: 99%
“…HCI research has focused on designing technologies that account for the challenges refugees face when they become refugees and as they transition into new host communities [2,4,11,12,14]. Al Mohammad & Vyas [2][3][4] highlighted that refugee experiences in Australia are characterized by social isolation, cultural barriers, mistrust, displacement trauma and shame when requesting help.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, studies have reported information deficit being a major challenge experienced by refugees as they journey to new countries [12,21]. Coles-Kemp et al [11] recount how refugees and asylum seekers feel a constant pressure to remain connected, often via mobile phones, to their previous lives and their new environments in order to cope with their new contexts. Design workshops in Za'atari camp in Jordan identified that refugee youth hope that technologies may aid in countering challenges they are experiencing such as inaccessible schooling [13].…”
Section: Introductionmentioning
confidence: 99%